A experiência de mães adolescentes cuidando de seus filhos nos primeiros seis meses de vida - Tomeleri, Keli Regiane (2007)
This study aims at understanding the experience of the adolescent mother with respect to child care in the first six months after birth and to identify how the nurse can assist the adolescent mother to construct this experience. It is a qualitative practice-converging field research that adopted the theoretical referentials of Culture Care Diversity in Nursing Practice and was developed in Cambé-Pr. Data were collected from February to October, 2007 by means of interviews and participative observation, accomplished in two steps: first at the maternity hospital and then at domicile, through 4 home visits. The informants were six mothers, of which 4 were followed until the sixth month, one for one month, one for a fortnight. Ages varied from 15 to 18. Four of the participants were primipara and two, bipara. Three of the adolescents did not live with the father of their child but with their family, though two of them maintained relationship with him. Five informants stopped formal education due to the pregnancy, the two who had their second child had already abandoned school when they first got pregnant. Only two wished to become pregnant, though none of the others used a proper method of prevention. Child care was experienced in different ways by each of the adolescent mothers. Four of them developed care securely and integrally from birth on and two felt fear and insecure during a one week adaptation period. Their mothers were their support and introduced them into child care practice. At the end of the first month, all felt secure and nursed the child integrally. In the fourth month they developed care independently, even conciliating this with other activities. In the sixth month they did not present difficulty at introducing complementary feeding and some resumed some of their life projects. During the sixth months of follow up, the children presented some health intercurrences; in most cases the mothers associated popular care practices to professional care. Some mothers faced intercurrences related to breast feeding, which interfered in the accomplishment of this activity and led to one case of cross feeding and three cases of ablactation. All attended their child well and most of the 9 actions intended care preservation. In some cases, accommodation was needed and in three, re-standardization. The family sustained care support and for most of the adolescents their mothers were their main reference. This study shows the importance for care practice to understand the experience of the adolescent mother in taking care of her child, being it necessary to recognize her care practice in order to develop care assistance compatible with the culture of the mother. The need for redefining thehealth professionals' attitude towards the adolescent mother and her family is evident. The challenge is to establish a bond with her, with her family and the supporting network involved as to maintaining reliable channel that helps them with popular and professional child care.